2007
DOI: 10.1152/ajprenal.00183.2005
|View full text |Cite
|
Sign up to set email alerts
|

Urine concentrating defect in prostaglandin EP1-deficient mice

Abstract: We investigated the role of the prostaglandin E2 (PGE2) EP1 receptor in modulating urine concentration as it is expressed along the renal collecting duct where argininevasopressin (AVP) exerts its anti-diuretic activity, and in the paraventricular and supraoptic nuclei of the hypothalamus where AVP is synthesized. The urine osmolality of EP 1-null mice (EP1 Ϫ/Ϫ ) failed to match levels achieved by wild-type (WT) counterparts upon water deprivation (WD) for 24 h. This difference was reflected by higher plasma o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 34 publications
(42 reference statements)
2
27
1
Order By: Relevance
“…In experimental glomerulonephritis, there was reduced urine osmolality, and overall renal damage was more acute in EP 1 (Ϫ/Ϫ) mice (Rahal et al, 2006). PGE 2 , via EP 1 , modulates urine concentration not modulated in the renal collecting duct but within the hypothalamus to promote arginine vasopressin biosynthesis in response to water deprivation (Kennedy et al, 2007). In a model of bladder outlet obstruction, detrusor hyperactivity was negligible in EP 1 receptor knockout mice (Schröder et al, 2004).…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%
“…In experimental glomerulonephritis, there was reduced urine osmolality, and overall renal damage was more acute in EP 1 (Ϫ/Ϫ) mice (Rahal et al, 2006). PGE 2 , via EP 1 , modulates urine concentration not modulated in the renal collecting duct but within the hypothalamus to promote arginine vasopressin biosynthesis in response to water deprivation (Kennedy et al, 2007). In a model of bladder outlet obstruction, detrusor hyperactivity was negligible in EP 1 receptor knockout mice (Schröder et al, 2004).…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%
“…EP 1 , expressed exclusively in collecting ducts, mediates PGE 2 -dependent inhibition of salt and water absorption. EP 1 -deficient mice have a urine concentration defect due to decreased vasopressin release, resulting in hypotension (16). EP 2 mRNA is present at low levels in the descending thin limb of Henle and the vasa recta of the outer medulla; mice deficient in EP 2 develop salt-sensitive hypertension.…”
Section: Renal Functionmentioning
confidence: 99%
“…Since urine has osmolalities that can vary from 50 to 1,000 mosmol/kg in humans and from 2,000 to 4,000 mosmol/kg in the mouse (16), widely fluctuating urea and NH 3 concentrations, and proton concentrations that vary over many orders of magnitude (pH 4.5-9), the bladder permeability barrier plays an essential role in osmotic and metabolic homeostasis. It has been shown that anxA4 binding and self-polymerization on membranes results in a rigidification of the lipids in the bound leaflet, with a resulting reduction in the permeability of the membrane to water and protons (11).…”
mentioning
confidence: 99%